Extracellular electron transfer via multiple electron shuttles in waterborne Aeromonas hydrophila for bioreduction of pollutants. Issue 12 (27th September 2021) - Min, Di; Liu, Dong‐Feng; Wu, Jie; Cheng, Lei; Zhang, Feng; Cheng, Zhou‐Hua; Li, Wen‐Wei; Yu, Han‐Qing
Abstract: Members of the genus Aeromonas prevail in aquatic habitats and have a great potential in biological wastewater treatment because of their unique extracellular electron transfer (EET) capabilities. However, the mediated EET mechanisms of Aeromonas have not been fully understood yet, hindering their applications in biological wastewater treatment processes. In this study, the electron shuttles in Aeromonas hydrophila, a model and widespread strain in aquatic environments and wastewater treatment plants, were explored. A. hydrophila was found to produce both flavins and 2‐amino‐3‐carboxy‐1, 4‐naphthoquinone (ACNQ) as electron shuttles and utilize them to accelerate its EET for the bioreduction of various pollutants. The Mtr‐like respiratory pathway was essential for the reduction of flavins, but not involved in the ACNQ reduction. The electron shuttle activity of ACNQ for pollutant bioreduction involved the redox reactions that occurred inside the cell. These findings deepen our understanding about the underlying EET mechanisms in dissimilatory metal reducing bacteria and provide new insights into the roles of the genus Aeromonas in biological wastewater treatment. Abstract : Multiple electron shuttles in waterborne Aeromonas hydrophila for bioreduction of pollutants were revealed in this study. The Mtr‐like respiratory pathway was essential for the reduction of flavins, but not involved in the ACNQ reduction. The electron shuttle activity of ACNQ for pollutant bioreduction involved the redox reactions that occurred inside the cell. This work provided new insights into the roles of the genus Aeromonas in biological wastewater treatment.